A STUDY ON THE PERFORMANCE OF THE E-PAYMENT SERVICES IN THIRUVANTHAPURAM DISTRICT - Shely R M1; G. Sreekanth (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The technological development in the financial system such as internet banking, e-payment technologies and information exchanges are related to significant increase in productivity due to improvement in services provided by banks. The reduction of costs of back office activities that represent the majority of banks operating costs, by switching from paper to e- payment instruments, has significant effects in the terms of gains in productivity and economies of scale. The advent of technology has led to the various changes in the society which has made people to spend more time on the internet. This has given the marketers a wonderful opportunity and a new media to promote their products and services through advertising on internet and banking sector is no exception to this. Banking sector has started using internet technology as a tool to upgrade the way they operate, deliver and compete against each other. As a result on-line banking has become the customer service trend for the financial institutions. Mass customisation happens effectively through on-line banking. Therefore, it becomes necessary to study the relevance of on-line banking in current banking scenario.